REVITALISASI RANTAI DISTRIBUSI BERBASIS KELEMBAGAAN SOSIAL: PEMBERDAYAAN EKONOMI PETANI JAGUNG - Setyawanto, Agus; Astutiek, Dwi; Hariyadi, Bachtiar; Ikhwandi, Ripin (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
The community engagement program aims to strengthen the bargaining position of corn farmers in Turen Subdistrict by revitalising a distribution system based on social institutions, particularly farmer cooperatives. The significance of this initiative lies in addressing the inequality in agricultural product distribution, which has long been dominated by middlemen, weakening farmers’ economic power. The approach employed is Participatory Action Research (PAR), which actively involves farmers in all stages, including problem identification, planning, implementation, and evaluation. The results show that establishing a participatory-based cooperative not only improves distribution efficiency and price transparency but also fosters social transformation, characterised by increased collective awareness, solidarity, and farmers’ independence in managing the distribution process. These findings reinforce the role of local institutions as a foundation for sustainable economic empowerment and demonstrate that participatory-based interventions are effective in building a fairer and more adaptive distribution system.